Identification of canine transmissible venereal tumor cells in the colostrum of a bitch - case report - A.S. Alves; O.M.M. Borges; E.L. Oliveira; A.M. Dantas Neto; K.P.G. Bezerra; M.P.A. Correia; G.N. Toledo; A.P. Souza (Arquivo Brasileiro de Medicina Veterinária e Zootecnia)
ABSTRACT Canine Transmissible Venereal Tumor (cTVT) is a contagious tumor in dogs. Commonly, it develops in the sexual organs including the potential to metastasize to the mammary gland. This report describes cTVT cells in the colostrum of a pregnant bitch with metastasis in the mammary gland. A three-year-old Dalmatian bitch was pregnant and presented nodules on the vagina dorsal floor and on the right cranial abdominal and left cranial abdominal mammary glands. Cytology of the nodules and the colostrum were performed. Cytological analysis identified cells from the cTVT, subtype plasmocyte cells (TVTcP). It was recommended to avoid breastfeeding of newborns because of the possibility of transmission to them, since cTVT is an easily transmissible tumor. The bitch was monitored to start the standard treatment for cTVT based on chemotherapy.